Structural basis of β-glucopyranoside salicin recognition by a human bitter taste GPCR - Xin Wang; Cui Zhou; Weizhen Ao; Lijie Wu; Yiran Wu; Weixiu Xu; Shenhui Liu; Qiwen Tan; Ling Wang; Fei Zhao; Junlin Liu; Yuan Pei; et al. (Cell Reports)
Summary: The human perception of bitterness is mediated by type 2 taste receptors (TAS2Rs), which recognize a broad array of bitter substances with distinct chemical properties. TAS2R16 exhibits a pronounced selectivity for β-glucoside-moiety-containing compounds, such as salicin from willow bark. However, the molecular mechanism of moiety-specific recognition and receptor activation in TAS2R16 remains unclear. Here, we present cryoelectron microscopy structures of the salicin-activated human TAS2R16 complexed with gustducin and Gi1 and Gi2 proteins. The binding mode of salicin with TAS2R16 and the specific interactions of the β-D-glucopyranoside moiety are detailed. Together with molecular docking and mutagenesis data, this study uncovers the structural underpinnings of TAS2R16’s group-specific recognition, receptor activation, and subsequent gustducin and Gi protein coupling. These findings advance our understanding of human bitter taste receptors and provide a foundation for structural modifications of bitter glycosides, opening potential therapeutic applications.